Impacts of SAYE PLUS, an Antimalarial Phytomedicine With Potential Anti-COVID-19, on the Physical, Biological, and Genotoxicity Parameters of Rodents in Short-Term Toxicity Studies - Joël Ouédraogo; Sylvain Ilboudo; Geoffroy Gueswindé Ouédraogo; Virginie Dakuyo; Salfo Ouédraogo; Gaétan D. Somda; Jean Claude Romaric Pingdwindé Ouédraogo; Moussa Ouédraogo; Rasmané Semdé; Sylvin Ouédraogo (Journal of Toxicology)
In response to the COVID-19 pandemic and following the World Health Organization’s call for action, several traditional medicine recipes were used without any scientific prerequisites concerning their safety. The current study investigated several short-term toxicity parameters of SAYE PLUS, an antimalarial phytomedicine used in COVID-19 patients in Burkina Faso. Following the guidelines of the Organisation for Economic Co-operation and Development (OECD), the safety profile of SAYE PLUS was investigated in a battery of tests in rats and mice. In an acute toxicity study, male and female rats received a single oral dose of 2000 mg/kg b.w. of the test substance. For the subacute toxicity test, male and female rats received daily oral doses of 250, 500, and 1000 mg/kg b.w. for 28 days. Acute and subacute toxicity tests were accompanied by food and water intake, body and organ relative weight, and blood chemistry of animals recording. In mutagenicity, sperm quality, and lipid peroxidation tests, mice were orally exposed to daily oral doses of 500, 1000, and 2000 mg/kg for seven days. Single dose of 2000 mg/kg b.w. of SAYE PLUS did not cause rats mortality. The LD50 is more than 2000 mg/kg b.w. Daily administration of SAYE PLUS for 28 days did not induce any significant change in the water or food intake and the body or organ relative weights of animals. Furthermore, no significant change was observed in biochemical parameters. In the test conditions, the recipe did not induce an increase of micronucleus or changes in sperm motility and number. However, all tested doses of SAYE PLUS induced a significant increase in MDA levels in mice serum. These results show that SAYE PLUS did not induce negative impacts on studied parameters, but the possible lipidic peroxidation observed must be further investigated for its mechanism and effects.